Pengaruh Digital Financial Literacy dan Adopsi Financial Technology Terhadap Kinerja UMKM di Labuhanbatu Dengan Akses Lembaga Keuangan Sebagai Variabel Moderasi - Riana Sitio; Tetty Rahmiati Harahap; Erni Wahyuni (Journal of Innovative and Creativity, 2025)
The development of the digital economy requires MSMEs to adopt financial technology and increase financial digital literacy. However, the effectiveness of these factors in improving the performance of MSMEs still shows inconsistent results in the empirical literature. This quantitative research uses a survey of MSME samples. Data were analyzed using regression analysis and moderated regression analysis (MRA) techniques to test the direct influence and moderation effect. The results of the study revealed that digital financial literacy and the adoption of financial technology did not have a significant direct effect on the performance of MSMEs. However, both variables have been shown to significantly increase access to financial institutions. The main finding of this study is that access to financial institutions not only has a positive and significant direct effect on performance, but also acts as a moderator that strengthens the influence of digital financial literacy and the adoption of financial technology on the performance of MSMEs. This study highlights the need for an integrated approach in MSME empowerment policies. Increased digital capabilities and technology adoption must be synergized with expanded access to formal finance to maximize its impact on improving business performance. For further research, it is important to consider mediation mechanisms and other contingency variables.